Testing the Efficacy of OurSpace, a Brief, Group Dynamics-Based Physical Activity Intervention: A Randomized Controlled Trial - Irwin, Brandon; Kurz, Daniel; Chalin, P.; Thompson, Nicholas (My University, 2017)
Background: Emerging technologies (ie, mobile phones, Internet) may be effective tools for promoting physical activity (PA). However, few interventions have provided effective means to enhance social support through these platforms. Face-to-face programs that use group dynamics-based principles of behavior change have been shown to be highly effective in enhancing social support through promoting group cohesion and PA, but to date, no studies have examined their effects in Web-based programs. Objective: The aim was to explore proof of concept and test the efficacy of a brief, online group dynamics-based intervention on PA in a controlled experiment. We expected that the impact of the intervention on PA would be moderated by perceptions of cohesion and the partner's degree of presence in the online media. Methods: Participants (n=135) were randomized into same-sex dyads and randomly assigned to one of four experimental conditions: standard social support (standard), group dynamics-based-high presence, group dynamics-based-low presence, or individual control. Participants performed two sets of planking exercises (pre-post). Between sets, participants in partnered conditions interacted with a virtual partner using either a standard social support app or a group dynamics-based app (group dynamics-based-low presence and group dynamics-based-high presence), the latter of which they participated in a series of online team-building exercises. Individual participants were given an equivalent rest period between sets. To increase presence during the second set, participants in the group dynamics-based-high presence group saw a live video stream of their partner exercising. Perceptions of cohesion were measured using a modified PA Group Environment Questionnaire. Physical activity was calculated as the time persisted during set 2 after controlling for persistence in set 1.Results: Perceptions of cohesion were higher in the group dynamics-based-low presence (overall mean 5.81, SD 1.04) condition compared to the standard (overall mean 5.04, SD 0.81) conditions (P=.006), but did not differ between group dynamics-based-low presence and group dynamics-based-high presence (overall mean 5.42, SD 1.07) conditions (P=.25). Physical activity was higher in the high presence condition (mean 64.48, SD 20.19, P=.01) than all other conditions (mean 53.3, SD 17.35).Conclusions: A brief, online group dynamics-based intervention may be an effective method of improving group cohesion in virtual PA groups. However, it may be insufficient on its own to improve PA. ©Brandon Irwin, Daniel Kurz, Patrice Chalin, Nicholas Thompson.
Citation: Irwin, B., Kurz, D., Chalin, P., & Thompson, N. (2016). Testing the efficacy of ourspace, a brief, group dynamics-based physical activity intervention: A randomized controlled trial. Journal of Medical Internet Research, 18(5). doi:10.2196/jmir.5342
Keywords: Cohesion; Group Dynamics; Internet; Physical Activity; Social Media; Social Support